PENGARUH BSI MOBILE DAN PELAYANAN TERHADAP KEPUASAN NASABAH (STUDI KASUS MAHASISWA/I PERBANKAN SYARIAH-UINSU) - Fachri Arrizki (EKSYA : Jurnal Ekonomi Syariah, 2023)
This study aims to find out and see how the influence and service of BSI Mobile has on customer satisfaction at UINSU Islamic Banking Students that are happening nowadays. BSI Mobile is a digital transaction tool from Bank Syariah Indonesia which aims to make it easier for customers to transact wherever and whenever. However, there are several customers who complain about the quality of BSI's mobile banking. whereas the best service should be provided to customers as an effort to improve customer satisfaction services in order to make customers comfortable in using the BSI Mobile. This study uses a qualitative method. Survey data in this study were obtained from 27 respondents. The results of this study are that more respondents are satisfied with the services provided by Bank BSI and make it easier for customers to access using BSI Mobile.